PROSES PERJANJIAN BAGI HASIL ATAS TANAH PERTANIAN DI DESA LIMEHE BARAT KECAMATAN TABONGO KABUPATEN GORONTALO - SILVANA ADELIYA MAHMUD; MUTIA CHERAWATY THALIB; ZAMRONI ABDUSSAMAD; MUHAMAD KHAIRUN KURNIAWAN KADIR; KARLIN Z. MAMU (Universitas Mahasaraswati K. Mataram, 2024)
A production sharing agreement is one of the transactions for cultivating agricultural land. This agreement is based on the basis of mutual assistance and a feeling of kinship which is still very strong among the people whose implementation is still not in accordance with existing provisions. This research aims to find out how the agricultural land production sharing agreement process is in West Limehe Village, Kec. Tabongo, Gorontalo Regency. The approach that has been implemented in scientific research is the Sociological Research Approach, which actually progresses the study of science in an expert way by directly exploring its objects. The research results show that the implementation of production sharing agreements on agricultural land in West Limehe Village, Kec. Tabongo, Gorontalo Regency was made unwritten only in verbal form on the basis of trust and agreement between the land owner and the cultivator, it was not carried out in front of the Village Head and no written deed or contract was made from this legal act